2021
DOI: 10.3390/coatings12010021
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Biomimetic Memristor Flexible Synapse

Abstract: With the development of the Internet of things, artificial intelligence, and wearable devices, massive amounts of data are generated and need to be processed. High standards are required to store and analyze this information. In the face of the explosive growth of information, the memory used in data storage and processing faces great challenges. Among many types of memories, memristors have received extensive attentions due to their low energy consumption, strong tolerance, simple structure, and strong miniat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 111 publications
(148 reference statements)
0
15
0
Order By: Relevance
“…The resistance recorded in the used memristors represents the logic state in the MAGIC implementation, where ROFF and RON represent logic "0" and "1," respectively. In [24,25] MAGIC NOR is employed as a foundation for performing logic computations inside the memory, hence increasing processing capabilities. To put it another way, each processing work is broken down into a series of MAGIC NOR operations that are carried out one after the other, employing memory cells as computation elements.…”
Section: ░ 2 Memristormentioning
confidence: 99%
“…The resistance recorded in the used memristors represents the logic state in the MAGIC implementation, where ROFF and RON represent logic "0" and "1," respectively. In [24,25] MAGIC NOR is employed as a foundation for performing logic computations inside the memory, hence increasing processing capabilities. To put it another way, each processing work is broken down into a series of MAGIC NOR operations that are carried out one after the other, employing memory cells as computation elements.…”
Section: ░ 2 Memristormentioning
confidence: 99%
“…Memristor can be a building block in neuromorphic systems by controlling conductance [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Various resistive switching behaviors are observed in a lot of materials, such as oxides, nitrides and other materials [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Among them, the indium gallium zinc oxide (IGZO)-based memristor is very promising for memory applications because of its interface-type switching and good compatibility with conventional Si processing [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, IGZO-based memristors have shown good synaptic properties for neuromorphic systems and memory applications [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Similarly to other oxide memristors, when Ag is used as the top electrode (TE) in IGZO-based memristors, Ag plays a dominant role in switching through the formation of the Ag filament [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Artificial synapse is the basis to construct artificial neural morphological networks at the physical level, which is one of the promising ways to overcome the existing von Neumann bottleneck and attracts more and more research efforts. Until now, a lot of artificial synapses with different structures and working principles have been reported, such as ferroelectric devices, phase change memory, , and field-effect transistors (FETs). Most of bio-synaptic functionalities, like short-term plasticity (STP) and long-term potentiation/depression (LTP/LTD), have been successfully simulated by these devices. …”
Section: Introductionmentioning
confidence: 99%